V knjižnici diši po praznikih - Rocek Bregar, Barbara (Šolska knjižnica, 2017)
The purpose of this paper is to shed light on a librarian's view on introducing elements of formative assessment into the school library. It presents three periods in the 3rd grade, which were planned by the librarian and teacher. In the school library, students learned about holidays. Special emphasis was placed on cooperative learning. The following elements of formative assessment were introduced into the learning process: determining prior knowledge, asking questions, shaping criteria for searching for literature in the school library, peer learning, evidence of learning, and feedback. It mostly highlights the advantages created by the library space and by learning in it.
Keywords: etnologija; formativno spremljanje; knjižnično informacijsko znanje; povratne informacije; preverjanje znanja; sodelovalno učenje; šolske knjižnice